The Effect of Service Quality on Customer Satisfaction At CV. Gumilar Putra Sumedang - Kurniasih, Nining; Hasanah, Rika Lutfiana Nur; Ratnasari, Shofia Annisa; Aliyah, Nur Asypah; Herdiansyah, Rahmat (Journal of Bussines Management Basic, 2025)
This research aims to find out the quality of service and customer satisfaction at CV. Gumilar Putra, as well as to determine the effect of service quality on customer satisfaction at CV. Gumilar Putra. The problem in this research is the decreasing number of CV customers. Gumilar Putra in 2023. This research uses quantitative methods. The sampling technique used in this research was incidental sampling with a total sample of 230 respondents. The data collection techniques used are interviews, questionnaires and observation. Statistical testing in this research used IBM SPSS for Windows 25 software. Data analysis used was normality test, heteroscedasticity test, autocorrelation test, simple linear regression analysis, Pearson correlation coefficient analysis, coefficient of determination analysis and hypothesis testing. The research results show that the implementation of service quality has good criteria with a total score of 14,193. Meanwhile, customer satisfaction has good criteria with a total score of 8,696. The magnitude of the influence of service quality on customer satisfaction is 37.4%, while the rest is influenced by other variables. Based on the hypothesis results, tcount > ttable (4.662 > 1.651564) is obtained, which means that the influence of service quality has a positive and significant effect on customer satisfaction.